The employment status, working conditions and social protection of vocational education trainees: The example of Finland - Rosin, Annika (SAGE Publications, 2026)
The employment status of trainees and its influence on labour and social security rights and working conditions is still an unresolved issue. This article analyses the employment status and rights of vocational education trainees in Finland in the light of the EÚs Quality Framework for Traineeships (QFT), and the proposals for a reinforced QFT and a Traineeships Directive. In Finland, vocational education trainees are explicitly excluded from the category of employees. It is argued that this exclusion is not in accordance with the practice of the Court of Justice of the EU or with Finland’s own definition of an employment relationship, and has negative effects on the labour rights and social protection of vocational education trainees. Non-employed vocational education trainees have only limited protection as regards their working time, health and safety, information and equality rights, and their social protection is weaker than that of employees. Nevertheless, due to the Finnish universal social protection system, vocational education trainees are covered by mandatory social protection, which fulfils the requirements of formality, effectivity, adequacy and transparency.